2019
DOI: 10.1017/s0033291719000035
|View full text |Cite
|
Sign up to set email alerts
|

Migration and psychosis: a meta-analysis of incidence studies

Abstract: BackgroundThe aims of this meta-analysis are (i) to estimate the pooled relative risk (RR) of developing non-affective psychotic disorder (NAPD) and affective psychotic disorder (APD) among migrants and their children; (ii) to adjust these results for socioeconomic status (SES); (iii) to examine the sources of heterogeneity that underlie the risk of NAPD.MethodsWe included population-based incidence studies that reported an age-adjusted RR with 95% confidence interval (CI) published 1 January 1977–12 October 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
143
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(156 citation statements)
references
References 84 publications
11
143
0
2
Order By: Relevance
“…We showed that a greater frequency of psychotic disorders typically observed in several ethnic minority groups (Selten et al, 2020) may be attributable to markers of social disadvantage and linguistic distance. The latter appeared to have stronger effects in firstgeneration migrants, while the former had greater magnitude amongst second-and later-generation ethnic minority groups.…”
Section: Discussionmentioning
confidence: 76%
“…We showed that a greater frequency of psychotic disorders typically observed in several ethnic minority groups (Selten et al, 2020) may be attributable to markers of social disadvantage and linguistic distance. The latter appeared to have stronger effects in firstgeneration migrants, while the former had greater magnitude amongst second-and later-generation ethnic minority groups.…”
Section: Discussionmentioning
confidence: 76%
“…The extent to which rates are elevated, relative to the majority population, varies considerably. For example, the highest reported rates are among Black minority groups (i.e., 4 to 6 times higher than in majority groups). This finding is driven in part by studies from the UK that report especially high rates for Black Caribbean and Black African populations.…”
Section: Variations By Ethnic Group: Incidence Of Psychotic Disordersmentioning
confidence: 99%
“…The place of migration may also matter. In the most recent review, for example, there was no strong evidence that rates of psychotic disorders were elevated in migrants to Canada or Israel.…”
Section: Variations By Ethnic Group: Incidence Of Psychotic Disordersmentioning
confidence: 99%
“…And although the causal mechanisms might not be fully understood, several well established risk factors for psychotic disorders could have important implications for primary prevention, such as social marginalisation and adversity, 11 high-potency cannabis use, 6 and migration. 12 However, assessment of the public health effects of these prevention efforts will not be possible without standardised and consistent metrics for population surveillance of psychotic disorders. Additionally, given the marked heterogeneity observed across countries and contexts, it is unlikely that a one size fits all public health solution will be effective, further highlighting the need for high quality standardised data as an important step towards a public health approach to psychotic disorders.…”
Section: Comment E213mentioning
confidence: 99%